2017
DOI: 10.1016/j.jhealeco.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring efficiency of health plan payment systems in managed competition health insurance markets

Abstract: Adverse selection in health insurance markets leads to two types of inefficiency. On the demand side, adverse selection leads to plan price distortions resulting in inefficient sorting of consumers across health plans. On the supply side, adverse selection creates incentives for plans to inefficiently distort benefits to attract profitable enrollees. Reinsurance, risk adjustment, and premium categories address these problems. Building on prior research on health plan payment system evaluation, we develop measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…Given that premiums in the Dutch health insurance market are community rated per health plan, overall payment system fit can be approximated by comparing the variation in financial result of Equation (3) with the variation in actual spending (Layton, Ellis, McGuire, & van Kleef, 2017). In a simulation of plan revenues and spending, we found that the four RA models together compensate for 29.8% of the squared deviations between individual-level spending and mean spending.…”
Section: Estimating the Risk Adjustment Model Of 2016mentioning
confidence: 99%
“…Given that premiums in the Dutch health insurance market are community rated per health plan, overall payment system fit can be approximated by comparing the variation in financial result of Equation (3) with the variation in actual spending (Layton, Ellis, McGuire, & van Kleef, 2017). In a simulation of plan revenues and spending, we found that the four RA models together compensate for 29.8% of the squared deviations between individual-level spending and mean spending.…”
Section: Estimating the Risk Adjustment Model Of 2016mentioning
confidence: 99%
“…When consumers take predicted use of services into account when choosing a health plan, they will be sensitive to differences in health plan design with regard to those services. Consequently, health insurers can influence the choice of consumers through health plan design [9,17,20,22,24]. McGuire et al [24] added estimated demand elasticities to the predictiveness/predictability measures by studying incentives for selection via plan design in a market with risk adjustment, and again confirmed that health insurers have incentives to deter bad risks through health plan design, specifically people with a chronic disease [24].…”
Section: Selection Via Plan Designmentioning
confidence: 99%
“…Because the sickest, highest-cost consumers who are most likely to trigger reinsurance payments are most likely in this part of the distribution, reinsurance may be able to complement risk adjustment by flattening this portion of the cost curve. Previous work suggests reinsurance performs well on various metrics of the performance of health plan payment systems with respect to adverse selection problems (Geruso and McGuire 2016; Layton et al 2017). …”
Section: Counterfactual Simulationsmentioning
confidence: 99%
“… 2 See Layton, Ellis, McGuire, and van Kleef (2017) in this issue for a recent review of this literature. …”
mentioning
confidence: 99%